2001
DOI: 10.1111/j.1469-7793.2001.00583.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in respiratory sensations induced by lobeline after human bilateral lung transplantation

Abstract: The sensations evoked by the injection of lobeline into the right antecubital vein were studied in 8 subjects after bilateral lung transplantation and 10 control subjects. In control subjects, two distinct sensations were experienced. There was an early noxious sensation (onset ≈10 s) followed by a late sensation of breathlessness (onset ≈26 s) associated with involuntary hyperventilation. The early sensation was accompanied by respiratory and cardiovascular changes. In contrast to control subjects, the early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 34 publications
0
23
1
Order By: Relevance
“…NCR of the α 7 subtype are an essential component in the mechanism of adaptation in low resistant rats. An in vitro (neocortex) and in vivo study (myocardium) showed that activation of α 7 NCR is analogues (1); highly resistant animals (2). Light bars, LS 1 after primary testing (random division of rats to low resistant and highly resistant specimens, n=11/10); dark bars, LS 2 after repeated testing in control groups (n=6/4); shaded bars, LS 2 in groups of HBH (n=5/6).…”
Section: Resultsmentioning
confidence: 98%
“…NCR of the α 7 subtype are an essential component in the mechanism of adaptation in low resistant rats. An in vitro (neocortex) and in vivo study (myocardium) showed that activation of α 7 NCR is analogues (1); highly resistant animals (2). Light bars, LS 1 after primary testing (random division of rats to low resistant and highly resistant specimens, n=11/10); dark bars, LS 2 after repeated testing in control groups (n=6/4); shaded bars, LS 2 in groups of HBH (n=5/6).…”
Section: Resultsmentioning
confidence: 98%
“…Some evidence suggests that relief of air hunger from lung and chest expansion is attenuated in lung transplant patients compared with heart transplant patients and healthy subjects, suggesting a greater role for pulmonary stretch receptors than chest wall receptors (103,111). However, these studies were performed before it was discovered that transplanted lungs are re-innervated quickly, and thus may have overestimated the contribution of chest wall receptors (112).…”
Section: Qualities Of Dyspneamentioning
confidence: 90%
“…It is well documented that humans are able to sense and evaluate respiratory changes such as those induced by respiratory loads, bronchoconstriction, lung volume, airway pressure, changes in ventilation and blood gas tensions (see Davenport et al, 2002), and by i.v. administrations of chemicals (Raji et al, 1995;Butler et al, 2001). However, little is known on sensations evoked by inhalation of tussigenic agents.…”
Section: Discussionmentioning
confidence: 99%